The lost stories - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2011)
Collects the lost stories of the Rangers who risked their lives to defend the kingdom, including the tales of the young warrior Horace, the courageous princess Evanlyn, the diplomat Alyss, and Will and his mentor, Halt.